The tumor microenvironment of metastatic osteosarcoma in the human and canine lung - L. E. McGee; J. S. Pereira; T. A. McEachron; C. Mazcko; A. K. LeBlanc; J. A. Beck (Communications Biology)
Abstract Osteosarcoma is a rare but aggressive bone tumor that develops spontaneously in human and canine patients and most commonly metastasizes to the lung. The presence of lung metastases significantly decreases the survival rate of patients, with minimal benefit seen with available treatments. Canine osteosarcoma is clinically and molecularly similar to human osteosarcoma and develops approximately ten times more frequently than human osteosarcoma making dogs a promising natural model to study disease progression. The development of new therapies for pulmonary metastases requires an understanding of the interplay between tissue resident cells as well as recruited cell types and how those interactions impact seeding and progression within the new metastatic site. This review explores the tumor microenvironment surrounding pulmonary metastases and how current knowledge in canine and human patients can inform better treatments and outcomes for both populations.